PENGARUH METODE PAIKEM DENGAN PEND EKATAN ROLE PLAY TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Via Chofifah Syabilla; Achmad Juhaeni; Nadrotul Uyun (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to identify the impact of the PAIKEM learning method (Active, Innovative, Creative, Effective, and Fun Learning) through role-play techniques on student learning outcomes in Islamic Religious Education (PAI) for Grade VIII students at SMP Negeri 12 Cilegon. The research method used is a quasi-experimental design with a pretest-posttest control group design. The subjects consisted of two groups, namely the experimental group taught using the PAIKEM method (role-play/drama) and the control group taught using the lecture method. The research instrument was a learning achievement test analyzed using an independent t-test. The results showed a significant improvement in the experimental group, where the average post-test score was higher than that of the control group. The experimental group obtained a final score of 17.2, while the control group achieved 10.9, indicating a difference of 6.3 points in favor of the experimental group. The t-test result produced a t-value of 5.432, which is greater than the t-table value of 2.06865 at a significance level of 0.05. Therefore, the null hypothesis was rejected and the alternative hypothesis was accepted. These findings indicate that the PAIKEM method with a role-play approach has a significant effect on improving student learning outcomes in cognitive, affective, and psychomotor aspects. This study is expected to serve as a reference for educators in enhancing the quality of Islamic Religious Education learning by implementing innovative and interactive teaching methods.